2010
DOI: 10.11609/jott.o2393.1268-72
|View full text |Cite
|
Sign up to set email alerts
|

Selection of egg attachment sites by the Indian Golden Gecko Calodactylodes aureus (Beddome, 1870) (Reptilia: Gekkonidae) in Andhra Pradesh, India

Abstract: InTRoduCTIonThe Indian Golden Gecko Calodactylodes aureus (Beddome, 1870) was rediscovered in 1986 after more than 100 years (Daniel et al. 1986;Russell & Bauer 1989). The genus Calodactylodes (Beddome, 1870) is restricted to tropical South Asia and is represented by two species: the Indian Golden Gecko Calodactylodes aureus (Beddome, 1870) and the Sri Lankan Golden Gecko Calodactylodes illingworthorum (Deraniyagala, 1953). The Indian Golden Gecko is distributed along the coastal hills of Andhra Pradesh, south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…This may be due to relatively lower predation pressure in crevices compared to the caves. Sreekar et al (2010) found that sites that have eggs attached to roofs of caves averaging more than three meters from the ground and that sites in which eggs were laid in crevices had greater success relative to the eggs that were laid at a distance less than one meter from the ground. The gecko has been reported to lay eggs mostly on vertical rocks (Sreekar et al, 2010) but we found that 71% of eggs were laid attached on the horizontal roof of caves and rock boulders.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…This may be due to relatively lower predation pressure in crevices compared to the caves. Sreekar et al (2010) found that sites that have eggs attached to roofs of caves averaging more than three meters from the ground and that sites in which eggs were laid in crevices had greater success relative to the eggs that were laid at a distance less than one meter from the ground. The gecko has been reported to lay eggs mostly on vertical rocks (Sreekar et al, 2010) but we found that 71% of eggs were laid attached on the horizontal roof of caves and rock boulders.…”
mentioning
confidence: 98%
“…In a few sites eggs were laid at an older egg deposition site. Sreekar et al (2010) found that viable eggs were only found during late June to September. In our study we noticed viable eggs between December 2010 and April 2011.…”
mentioning
confidence: 99%
See 3 more Smart Citations